Federal Government Task Force on Labour Relations - Woods, H. (Relations industrielles / Industrial Relations, 1967)
In December 1966, Prime Minister Pearson announced the creation of a Task Force on Labour Relations. Under the chairmanship of H.D. Woods, Dean, Faculty of Arts and Science, McGill University, Montréal, the members are: Gérard Dion, Professor, Department of Industrial Relations, Laval University, Québec; John H.G. Crispo, Director, Centre for Industrial Relations, University of Toronto; A.W.R. Carrothers, Dean, Faculty of Law, University of Western Ontario.